The tidal waves of connected health devices with healthcare applications: consequences on privacy and care management in European healthcare systems. Issue 1 (December 2017) - Allaert, Francois-André; Mazen, Noël-Jean; Legrand, Louis; Quantin, Catherine
Abstract Background The market for Connected Health Devices (CHD) with healthcare applications is growing fast and should be worth several billion euros in turnover in the coming years. Their development will completely transform the organisation of our healthcare system, profoundly change the way patients are managed and revolutionizes disease prevention. Main body The CHD with healthcare applications is a tidal wave that has societal impact calling into question the privacy of patients' personal and healthcare information and its protection in secure systems. Rather than trying to stop the use of CHD, we must channel the wave by clearly examining the advantages versus the risks and threats to the patients, and find counter-measures for implementation. The main difficulty is channeling the wave in a way that is acceptable to CHD developers who otherwise will bypass the rules, even if they can be sued for it. Therefore, it appears necessary to implement guidelines that can be used by all developers, defining the minimum requirement for assuring the security of patient privacy and healthcare management. Conclusion In European Healthcare Systems, there is an imperative need for establishing security guidelines that CHD producers could use to ensure compliance, so that patient privacy and healthcare management is safeguarded. The aim would be to implement the guidelines a posteriori rather than a priori control so as not to hamper innovation.